Two-photon-pumped high-quality, single-mode vertical cavity lasing based on perovskite monocrystalline films. (February 2020) - Li, Xiaohong; Liu, Weiwei; Song, Yiling; Long, Hua; Wang, Kai; Wang, Bing; Lu, Peixiang
Abstract: Single-mode microlasers are of crucial importance for high-performance integrated photonic devices. However, it still remains a significant challenge to achieve single-mode microlasers conveniently. In this work, we propose a strategy to realize high-quality, single-mode vertical-cavity surface-emitting lasers (VCSELs) based on hybrid perovskite monocrystalline films. Under two-photon pump, the VCSEL exhibits excellent performances with a remarkable low threshold of 421 μJ/cm 2, a high quality factor (Q factor) of 1286 and a small divergence angle of 0.5°. Importantly, single-mode lasing with a good spatial coherence can be conveniently achieved with the VCSEL configuration, which significantly reduces the complexity for fabricating high-quality single-mode microlasers. In addition, switchable VCSEL can be realized by taking advantage of the anisotropic two-photon absorption of the hybrid perovskites. The single-mode vertical-cavity emission, excellent lasing performances, frequency up-conversion ability and switchable property will provide a versatile platform for high-performance nanosources and multifunctional integrated optoelectronic devices. Graphical abstract: Two-photon-pumped high-quality, single-mode vertical-cavity surface-emitting lasers (VCSELs) are realized based on hybrid perovskite monocrystalline films. The single-mode VCSEL exhibits a low threshold of 421 μJ/cm 2, a high quality factor (Q factor) of 1286 and a small divergence angle of 0.5°. Image 1 Highlights: Two-photon pumped VCSELs are realized by integrating large-area, high-quality MAPbBr3 monocrystalline films with microcavity. The VCSEL exhibits a low threshold of 421 μJ/cm 2, a high quality factor of 1286 and a small divergence angle of 0.5°. Switchable VCSELs are demonstrated by taking advantage of the anisotropic two-photon absorption of the hybrid perovskites.